N-acetylcysteine, an antioxidant with anti-adipogenic effect on adipocytes - Pieralisi, Azul (2017)
Reports about antioxidant effect in obesity are contradictory. We showed that N-acetylcysteine (NAC) inhibits cellular lipid accumulation during adipocyte differentiation, through the inhibition of adipogenic transcriptor factors expression, such as PPARγ and, MAPKs phosphorylation (Pieralisi et al,Redox Biol 2016; Soto el al,Redox Rep 2016). Here we evaluated NAC on fully differentiated cells (3T3-L1 adipocytes: AC). Treatments with 0.01 to 5 mM NAC, included in culture media for 5 days, were not toxic. 5mM NAC treatment on AC (ACN) provoked a decrease of 60% in cellular Triglycerides (Tg) content (1.22+0.09 gTg/g protein [AC] vs 0.49+0.03 gTg/g protein [ACN], p<0.05). We evaluated Oil-Red-O stained lipids content in ACN comparing to AC, which is set to 100 (100+4 [AC] vs 80+2 [ACN] arbitrary units (AU), p< 0.05), lipid protein perilipin (Pl) mRNA levels (Pl/ Rplp0:100+13 [AC] vs 72+9 [ACN] AU, p< 0.05) and PPARγ: protein expression (PPARγ/GAPDH:100+6 [AC] vs 70+4 [ACN]AU; p< 0.05) and mRNA levels (PPARγ/Rplp0:100+7 [AC] vs 74+14 [ACN]AU, p<0.05). These NAC treatments produced a decrease of 20 ? 30%, suggesting that NAC could inhibit new lipid production. We developed liposome of 100nm diameter (LIP) including 5mM NAC, as better tool for NAC administration. Phase transition enthalpy decreased from 3.86 J/g in LIP to 3.25 J/g in LIP+NAC, indicating NAC incorporation.